Pengaruh Literasi Zakat dan Kepercayaan pada Lembaga Pengelola Zakat Terhadap Perilaku Membayar Zakat Muzakki di Kota Jambi Tahun 2021- 2022 - Irsyad, Muhammad; Wediawati, Besse; Solikhin, Agus (Indonesian Journal of Islamic Economics and Business, 2023)
This study aims to examine the effect of zakat literacy and trust in zakat management institutions on the behavior of paying zakat muzakki in the city of Jambi. This research is quantitative and the research data used are primary and secondary data. The population in this study is muzakki, namely someone who is obliged to pay zakat in the city of Jambi. Samples were taken using Stratified Random Sampling, totaling 90 people. Data was collected through the distribution of questionnaires with a Likert scale. The data testing technique uses Validity Test and Reliability Test, R-Square Test and Hypothesis Testing with Bootstrapping using SmartPLS 3.0 Software. The results showed that zakat literacy had a positive and significant effect on the behavior of paying zakat muzakki in the city of Jambi and trust in zakat management institutions had a positive and significant effect on the behavior of paying zakat muzakki in the city of Jambi.